EFFECT OF TREATMENT WITH GROWTH-REGULATORS AND SCARIFICATION ON THE TOLERANCE TO WATER-STRESS IN SEEDS OF ORYZA-SATIVA LCVIAC-165 - Takaki, M. (Inst Tecnologia Parana, 1994)
The effect of treatment of seeds of Oryza sativa L. cv. IAC 165 with gibberellic acid, 6-benzyladenine and ethrel on the tolerance to the water stress were analysed. Gibberellic acid had no effect and 6-benzyladenine and ethrel promoted slight increase in the tolerance to water stress, specially in darkness. After scarification, those growth regulator presented no effect. Our results suggest that 6-benzyladenine and ethrel promoted water stress tolerance due to the decrease in the resistance of the seed coat to embryo expansion.
Keywords: SEED GERMINATION; WATER STRESS; GROWTH REGULATORS; ORYZA-SATIVA